RESPONSES OF COTTON APHID APHIS GOSSYPII AND ITS PREDATORS TO VOLATILE ORGANIC COMPOUNDS EMITTED FROM INFESTED AND UNINFESTED CUCUMBER PLANTS - Salim , Hind; Ahmed , Qasim; Du, Xin; Ren, Yonglin (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The response of cotton aphid Aphis gossypii adults and their predators Coccinella septempunctata and Chrysoperla carnea to infested or uninfested cucumber leaves was tested using a Y-shape olfactometer. Aphids were significantly more attracted to uninfested than infested cucumber leaves. C. septempunctata was significantly more attracted to the infested leaves with aphids than uninfested cucumber leaves. At the same time, C. carnea responded to VOCs from leaves infested with aphids compared to healthy leaves. Moreover, the feeding activity of aphids rustles to release Kairomonal compounds, which can be positively exploited by C. carnea to identify the location of aphids and infested plants. Our results indicated that predators could distinguish between infested and uninfested leaves, and their responses were significant to the differentially released VOCs from infested plants. VOCs were extracted using HS-SPME from A. gossypii-uninfested and infested cucumber leaves and analyzed by gas chromatography-mass spectrometry. 35 compounds were identified in uninfested and infested leaves; 7 VOCs were detected in infested cucumber leaves and were not detected in uninfested leaves. In conclusion, the findings from the current study on how cotton aphids and predators respond to infested leaves compared with uninfested leaves and clean air are due to the emission of volatile organic compounds that reflect the traits of the plant host